SINO-KOREAN VOCABULARY LEARNING STRATEGIES AMONG INDONESIAN KOREAN LANGUAGE LEARNERS - Alfiani Rahmi Chandraswara; Usmi Usmi (Language Literacy: Journal of Linguistics, Literature, and Language Teaching)
This study investigates the vocabulary learning strategies employed by students at Universitas Indonesia in acquiring Sino-Korean vocabulary—an essential component of the Korean language derived from Chinese characters (Hanja). Given the prevalence of Sino-Korean words in university-level Korean language materials, understanding effective learning strategies is crucial. A quantitative research design was adopted, using questionnaires to gather data on students’ learning approaches and experiences. The data were analyzed using SPSS version 29.0, with mean (M) and standard deviation (SD) computed for each strategy. The results indicate that students predominantly rely on memory-based strategies, such as recalling vocabulary encountered in texts or song lyrics. Among the five strategy categories, metacognitive strategies were the least frequently used overall. However, one metacognitive approach—learning vocabulary through exposure to media (e.g., movies, news, and music)—emerged as the most commonly applied individual strategy. These findings provide meaningful implications for educators and curriculum developers aiming to enhance vocabulary instruction in Korean language programs, particularly in supporting the acquisition of Sino-Korean vocabulary.